2020
DOI: 10.1186/s12870-020-02360-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of Striga resistance in early maturing white tropical maize inbred lines

Abstract: Background: Striga hermonthica (Benth.) parasitism militates against increased maize production and productivity in savannas of sub-Saharan Africa (SSA). Identification of Striga resistance genes is important in developing genotypes with durable resistance. So far, there is only one report on the existence of QTL for Striga resistance on chromosome 6 of maize. The objective of this study was to identify genomic regions significantly associated with grain yield and other agronomic traits under artificial Striga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
62
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 58 publications
(79 reference statements)
10
62
3
Order By: Relevance
“…These results agreed with previous findings that tropical maize germplasm is highly diverse with H e > 0.3 [37][38][39]. The mean PIC obtained in the present study, 0.29 using 5974 DArTseq SNPs for the 208 maize accessions was higher than the 0.19 and 0.26 reported for tropical early-maturing maize inbred lines using 15,047 [30] and 7224 SNPs for a sample size of 94 and 134, respectively [20,27]. The discrepancies between the results of our study and those of earlier researchers may be due to the use of different genetic materials, the sample sizes, and the number of SNPs used.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results agreed with previous findings that tropical maize germplasm is highly diverse with H e > 0.3 [37][38][39]. The mean PIC obtained in the present study, 0.29 using 5974 DArTseq SNPs for the 208 maize accessions was higher than the 0.19 and 0.26 reported for tropical early-maturing maize inbred lines using 15,047 [30] and 7224 SNPs for a sample size of 94 and 134, respectively [20,27]. The discrepancies between the results of our study and those of earlier researchers may be due to the use of different genetic materials, the sample sizes, and the number of SNPs used.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the estimated diversity indices revealed ample genetic diversity within the maize panel indicated by average H e (0.36) and H o (0.5). The He obtained in this study was comparable to the 0.36 reported for provitamin A (PVA) quality protein maize (QPM) germplasm from IITA-MIP [21] but was higher than that reported for maize landraces from Eastern Africa (H e = 0.25), Western Africa (H e = 0.18), and Sahel Africa (H e = 0.24) [9] as well as tropical maize breeding populations (H e = 0.22) [27] including IITA early-maturing white inbred lines [20]. Characterization of the Burkinabe, Ghanaian, and Togolese maize pools showed different values for the estimated diversity indices.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Seven of the fourteen QTLs identified across environments had their marker intervals greater than 4cM from their linked markers, implying that it is necessary to further fine map these chromosomal regions to reduce the marker intervals [ 33 ]. The QTL qsd-3 and qsd-9 identified in the present study were found to be in the same region with those reported by Adewale et al [ 38 ] on chromosomes 3 and 9, respectively. In contrast, QTL identified in the present study for Striga resistance/tolerance traits are different from those earlier reported by Badu-Apraku et al [ 39 ] in an extra-early maturing yellow F 2:3 mapping population.…”
Section: Discussionsupporting
confidence: 91%
“…These two QTLs accounted for 55 per cent of the phenotypic variation (PV) with predominance of dominance genetic effects over additive genetic effects in the expression of the two Striga resistant QTLs. Similarly, Adewale et al [ 38 ] identified significant loci on chromosomes 9 and 10 of maize, closely linked to ZmCCD1 and amt5 genes, respectively which could be related to plant defense mechanisms against Striga parasitism. In another study, Badu-Apraku et al [ 39 ] identified twelve QTLs for four Striga resistance/tolerance adaptive traits in an F 2:3 mapping population involving the Striga resistant inbred line TZEEI 79 and the Striga susceptible inbred TZdEEI 11.…”
Section: Introductionmentioning
confidence: 99%